Comparison of venous repair results using either arterial or vein grafts in a crush-avulsion injury model - ŞİRVAN, Selami Serhat (Turk J Med Sci, 2019)
BACKGROUND/AIM: Venous insufficiency after replantation or revascularization is one of the most common causes of limb loss in either the short or the long term. The aim of this study was to evaluate the results of a new technique to overcome venous insufficiency. MATERIALS AND METHODS: A crush-avulsion type of injury was formed in the femoral veins of rats of 3 separate groups. In the control group, primary repair was applied to the damaged veins and the remaining 2 groups were repaired with either an arterial graft or a vein graft. The success rates of anastomosis were then compared. RESULTS: In the control group the patency rate was 25% in the 2nd hour, 12.5% on the 2nd day, and 12.5% on the 10th day. The patency rate in the vein group was 87.5% in the 2nd hour, 50% on the 2nd day, and 37.5% on the 10th day, whereas the patency rates in the artery group were 100% in the 2nd hour, 87.5% on the 2nd day, and 75% on the 10th day. CONCLUSION: Microsurgery requires experience and patience. It can be considered that the use of arterial grafts for venous repair in replantation after crush-avulsion type amputations can increase the success rate of replantation.